Phenomenology of Flow Experience in BPO Sector: Empirical Study - Mahajan, Goldy; Mehta, Versha (Gyan Management Journal, 2012)
Motivating employees is an incessant and key processforany industry. No amount of quality work can obtained from employees unless they feel motivated enough to pour their heart and soul into what they do. The concept of motivating employees becomes all the more important for the BPO industry where the job involves a high degree of monotony and tremendous amount of stress while working during odd hours of the night. Flow is a certain kind of intrinsic motivation that someone can feel. It occurs when someone feels an overall, intrinsically motivated feeling when they are totally involved in (m activity and are on "auto pilot" and performance is an extremely important criterion that relates to organizational outcomes and success. Keeping in view the problems faced by the BPO's the present study is conducted to measure flow of BPO employees & its impact on the performance by using flow construct model.
Keywords: Flow experience; Flow; performance; on line environment